Studi Steganografi Pada Citra Digital Menggunakan Shuffled Singular Value Decomposition (SSVD) - Ainiya Fahrurosi Aziza; Elly Matul Imah (Limits: Journal of Mathematics and Its Applications, 2019)
Stegangraphy is a technique for embed secret message in original image. It has an important role in the field of information hiding for secret communication. Many research about steganograph y tecniques have been developed, one of them is singular value decomposition (SVD). SVD method is popular discused in many tecnique such us steganography and watermarking. In addition to SVD there is a method which can give better result than SVD on watermaring technique that is Shuffled SVD. The differences between SSVD and SVD is in shuffle process which applied before applying SVD. The popularity of SSVD in the watermarking technique made the writer intererest to propose an image steganography tecnique using shuffled singular value decomposition (SSVD). The data used are two original RGB imaage and a message RGB image. Quality measured by PSNR and Correlation Coefficient. The experimental result show that the shuffling process on the secret message caused embedded message can’t read easyly so the secret message is more secure.